Association between ACE, ACTN3, AGT, BDKRB2, and IL-6 gene polymorphisms and elite status in Colombian athletes - González-Estrada, G. D.; Berrio, G. B.; Gómez-Ríos, D. (Journal of Physical Education and Sport, 2023)
In Colombia and Latin America, there is a lack of knowledge of the genetic potential of high-performance athletes. Currently, genotypes of athletes of different ethnicities have been characterized, especially in Europe, North America, and Asia. It is known that genetic polymorphisms generate protein variants that potentially favor performance in sport and physical activities. In this contribution, 225 Colombian elite athletes were sampled as well as an equal number of controls. The elite group included athletes of Olympic, Pan-American, and World levels and the controls were individuals with regular physical activity but not high-level competitors. ACE, ACTN3, AGT, BDKRB2, and IL-6 genes were analyzed for genotypic characterization. Polymorphism frequencies were assessed for a 95% significance to establish the association of genotype with the elite athlete status. Significant differences were found between elite athletes and controls for the homozygous genotypes DD (p < 0.001) and II (p < 0.001) of the ACE gene, and the homozygous (CC and TT) and heterozygous genotypes of the AGT gene. No significant differences were found for the evaluated genotypes of the ACTN3, BDKRB2, and IL-6 genes between elite athletes and controls. ACE D (p < 0.001, odds ratio = 2.08) and AGT C (p < 0.001, odds ratio = 2.45) alleles were associated with the elite athlete status. The ACTN3R, BDKRB2-9, and IL-6 C alleles, which have been previously suggested as positive genetic markers of athletic performance, were more frequent both in the athletes and controls. Although no significant differences were found, this fact does not negate positive effects of carrying those alleles on athletic performance.